Osmolytes and CsAQP expression jointly influence water physiology in the peel and pulp of orange (Citrus sinensis (L.) Osbeck) fruit during postharvest water loss - Lin, Xiong; Wei, Qingjiang; Zeng, Lingcai; Zhan, Minxuan; Li, Feng; Chen, Jinyin; Ma, Qiaoli (Frontiers in Plant Science, 2024)
Water loss is a serious issue affecting the quality of postharvest horticultural products. Aquaporins (AQPs) regulate the transport of water across biological membranes, along the gradient of water potential, and may play a role in water loss. In this study, matured orange fruits (Citrus sinensis) stored at ambinent temperature (RH 85-95%) for 105 d showed that the weight loss persistently increased, and its rate peaked at 45–60 d and 90–105 d. Both water content and potential were higher in the pulp than in the peel. Water content rose before 60 d, and peel water potential fell with an increased gradient after 60 d. Comparing with peel, osmolytes such as soluble sugar, sucrose, glucose, fructose, and organic acids showed higher accumulation, and their levels were the lowest around 60 d. In contrast, soluble protein and inorganic minerals showed low levels of accumulation in the pulp. In total, 31 CsAQP genes were expressed in the fruit, and most of them were down-regulated in the peel but up-regulated in the pulp during storage. These genes were subsequently classified into four clusters based on their expression patterns. Genes in Cluster I — including CsNIP1;1/2;1/2;2/2;3/3;1/4;1/6;1, CsTIP1;3/2;2/2;3/5;1/6;1, CsXIP1;1/1;2, CsSIP1;2, and CsPIP1;2 — were persistently up-regulated in the pulp for the 105 d of storage, especially at day 60, when some genes showed 103-fold higher expression. Pearson’s correlation and principal component analysis further revealed a significant positive correlation among weight loss rate, water content, and water potential gradient (R2 = 0.85). Indexes positively correlated with osmolyte content and Cluster I gene expression in pulp samples suggest that increased CsAQP gene expression in pulp is linked to faster water loss in oranges, particularly at 60 days postharvest.